Penyuluhan Machine Learning dan Quantum Artificial Intelligence di Era Industri 4.0 - Hendra Bunyamin; Teddy Marcus Zakaria; Andreas Widjaja; Natanael Halim; Vania Sarwoko (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2021)
The Digital Era 4.0 has started since 2016 and two Southeast Asia countries such as Malaysia and Singapore have already adapted to the era; unfortunately, Indonesia has been struggling to adapt the era and, therefore, needs to catch up the digital competitiveness of its neighbouring countries. According to IMD World Digital Competitiveness 2020, Indonesia placed 56th of 63 countries in the digital competitiveness measurement. Despite its poor performance, Indonesia can catch up with other countries by starting from universities’ environment where Indonesia’s next generations study. Universities are prominent education institutions which prepare next generations for world digital competitiveness. According to BPS Indonesia, the unemployment of bachelor, master, and doctoral graduates reach a total number of 737.000, or 5,67% of 13 millions work force. One of the causes is the lack of technological knowledge, specifically, Artificial Intelligence (AI), from the graduates. Particularly, when they become business leaders, they are not fully prepared to create new job openings because mostly their mindsets are to find suitable jobs after study. The two webinars are results of collaboration between several universities which form NUNI (Jejaring Universitas Nusantara) whose purpose is to equip students with the knowledge of AI. Our method of counselling whose format is two webinars with both titles are Interpretable Machine Learning and Quantum Artificial Intelligence has gained appreciation in the form of average participation score which approaches excellent score (4,60 of 5,00). Additionally, these two webinars are publicly available in web blogs and Youtube videos.